1994
DOI: 10.1002/j.1460-2075.1994.tb06626.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of high affinity human antibodies directly from large synthetic repertoires.

Abstract: Antibody fragments of moderate affinity (approximately microM) can be isolated from repertoires of approximately 10(8) immunoglobulin genes by phage display and rounds of selection with antigen, and the affinities improved by further rounds of mutation and selection. Here, as an alternative strategy, we attempted to isolate high affinity human antibodies directly from large repertoires. We first created highly diverse repertoires of heavy and light chains entirely in vitro from a bank of human V gene segments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
537
1
3

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 916 publications
(555 citation statements)
references
References 75 publications
14
537
1
3
Order By: Relevance
“…The dissociation constant of CEA6 for CEA is in the nanomolar range (7.7 x 10-9 M), which is typical of antibodies isolated from very large repertoires (Perelson and Oster, 1979;Griffiths et al, 1994;Vaughan et al, 1996). Our early work showed that the antibody binds CEA-expressing cells by flow cytometry and immunocytochemistry, and localizes to CEA-expressing human tumour xenografts in nude mice.…”
Section: Discussionmentioning
confidence: 95%
“…The dissociation constant of CEA6 for CEA is in the nanomolar range (7.7 x 10-9 M), which is typical of antibodies isolated from very large repertoires (Perelson and Oster, 1979;Griffiths et al, 1994;Vaughan et al, 1996). Our early work showed that the antibody binds CEA-expressing cells by flow cytometry and immunocytochemistry, and localizes to CEA-expressing human tumour xenografts in nude mice.…”
Section: Discussionmentioning
confidence: 95%
“…2A, curves b,c). This was unexpected as the rotational correlation time of a scFv molecule can be calculated according to Visser et al [17] as [10][11][12][13][14][15][16][17][18][19][20] ns. It appears that this discrepancy may be due to association of scFv molecules by hydrophobic interactions in the presence of salt, as in experiments performed in the absence of NaC1 (%crv shifts to about 20 ns (data not shown).…”
Section: Characterization Of Scfv Fragmentsmentioning
confidence: 99%
“…The theoretical advantages of recombinant human antibodies over mouse monoclonals as therapeutic agents are well recognized [1][2][3][4][5]. However, the optimal source of immunoglobulin genes for the construction of these libraries remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has recently been demonstrated that the retrieval of specific antibodies can be enhanced by increasing the library size and by using synthetic immunoglobulin genes [3,4,8]. The diversity and size of synthetic libraries, and thus the affinity of particular antibodies, can be further increased by combinatorial infection and in vitro recombination strategies [3,9,10]. However, this artificial construction of large non-immune libraries is technically challenging and introduces a number of potential problems.…”
Section: Introductionmentioning
confidence: 99%